1969
DOI: 10.1017/s0021932000007173
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of child growth in a rural community in Jamaica

Abstract: A longitudinal study of the growth of a cohort of 229 infants born in a rural area in Jamaica and followed to their 4th birthdays is described, and this paper reports analyses of the anthropometric measurements.Moderate impairment of growth affected the majority of children and was most marked between the ages of 3 and 15 months. Severe impairment occurred in boys more often than girls and in this comm unity was rarely attributable to disease.The concept of weight faltering has been investigated in some detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1969
1969
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This has been reported by other investigators as well. In a study from Jamaica, while about 21% of the children under one year old showed some degree of malnutrition by Gomez's classification, more than half of those over one year old were in this category [6] Earlier studies conducted in Jamaica reported a similar pattern [7,8]. It has been hypothesized that the better nutritional status of infants is probably due to their being able to satisfy their nutritional needs through breast milk and some complementary foods.…”
Section: Discussionmentioning
confidence: 96%
“…This has been reported by other investigators as well. In a study from Jamaica, while about 21% of the children under one year old showed some degree of malnutrition by Gomez's classification, more than half of those over one year old were in this category [6] Earlier studies conducted in Jamaica reported a similar pattern [7,8]. It has been hypothesized that the better nutritional status of infants is probably due to their being able to satisfy their nutritional needs through breast milk and some complementary foods.…”
Section: Discussionmentioning
confidence: 96%
“…In the private establishment children were asked their date of birth. Since lung function during childhood has been reported to be better correlated with stature than with age (Cotes, 1975), and rural children tend to be shorter than urban children relative to chronological age (Ashcroft and Lovell, 1964;Standard et al, 1969), height differences between the groups were minimised by selecting the rural group to be about 6 to 9 months older than the urban group.…”
Section: Methodsmentioning
confidence: 99%
“…Many investigations, e.g. Standard, Desai & Miall (1969), have shown that, in the West Indies, the most critical time in child upbringing is in late infancy. In that period, mortality is relatively high and growth increments are low compared to those in more favoured countries.…”
Section: Discussionmentioning
confidence: 99%